First isolation of Photobacterium damselae ssp. damselae from cultured redbanded seabream, Pagrus auriga Valenciennes, in Spain - Labella Vera, Alejandro Manuel; Alonso-Sánchez, María del Carmen; Infante, Carlos; Cardenas, Salvador; López-Romalde, Sonia; Machado, Manuel; Borrego-García, Juan José (Blackwell Publishing Ltd, 2006)
This is the first report of the isolation of P. damselae ssp. damselae from redbanded seabream, a sparid fish newly cultured in southern Spain. A low variability in the biochemical profile among the P. damselae ssp. damselae isolates tested was observed (acetoine production), although these profiles were clearly different from that of P. damselae ssp. piscicida. The analysis of ureC and 16S rRNA genes confirmed the phenotypic characterization of the isolates as P. damselae ssp. damselae.
Keywords: Microbiología; Peces - Microbiología; Multiplex-polymerase chain reaction; Pagrus auriga; Photobacterium damselae ssp. damselae; 16S rRNA; ureC; Spain